Validity evidence of the Edinburgh Postnatal Depression Scale: an integrative review - Silva, Renata Costa da; Oliveira, Nayara de Jesus; Silva, Joise Magarão Queiroz; Rosa, Renata Fernandes do Nascimento; Marques, Patrícia Figueiredo; Freitas, Katia Santana; Coelho, Edméia de Almeida Cardoso (O Mundo da Saúde, 2025)
The prevalence of common mental disorders, including depression, post-traumatic stress disorder, obsessive-compulsive disorder, and a variety of anxiety disorders, represents a major global burden of disease in both high- and low-income countries. This study aimed to identify validity evidence of the Edinburgh Postnatal Depression Scale (EPDS) tested in puerperal women. An integrative review was conducted using the PICO strategy to construct the research question: What validity evidence is available for the Edinburgh Postnatal Depression Scale in puerperal women? The databases searched were PubMed, CINAHL, Embase, Scielo Org., and SCOPUS. Screening was carried out in Rayyan, following the PRISMA 2020 flowchart. Searches were conducted from october to november 2022. Based on inclusion criteria, 17 studies were selected for analytical synthesis. The Edinburgh Postnatal Depression Scale is widely recognized as the gold standard for detecting postpartum depression in women worldwide. This instrument allows the identification of depression risk through different cutoff scores. Understanding how the EPDS functions and its limitations is essential for its effective use across diverse contexts, ensuring accurate screening and early identification of cases requiring specialized follow-up.